Shop manual for automotive brake systems - Eichhorn, Lane; Erjavec, Jack; Corinchock, John A. (Today's technician, 1996)
This volume of the Today's Technician Series details the latest technology in brakes systems as well as thorough coverage of environmental and safety issues, including the latest in anti-lock brake systems.